PET 6-[18F]fluoro-L-m-tyrosine studies of dopaminergic function in human and nonhuman primates - Eberling, Jamie L.; Bankiewicz, Krystof S.; O’neil, James P.; Jagust, William J. (Frontiers in Human Neuroscience, 2008)
Although positron emission tomography (PET) and the aromatic L-amino acid decarboxylase (AADC) tracer 6-[18F]fluoro-L-m-tyrosine (FMT) has been used to assess the integrity of the presynaptic dopamine system in the brain, relatively little has been published in terms of brain FMT uptake values especially for normal human subjects. Twelve normal volunteer subjects were scanned using PET and FMT to determine the range of normal striatal uptake values using Patlak graphical analysis. For comparison, seven adult rhesus monkeys were studied and the data analyzed in the same way. A subset of monkeys that were treated with a unilateral intracarotid artery infusion of the dopamine neurotoxin MPTP showed an 87% decrease in striatal FMT uptake. These findings support the use of PET and FMT to image AADC distribution in both normal and diseased brains using Patlak graphical analysis and tissue input functions.